2020
DOI: 10.18016/ksutarimdoga.vi.692756
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Fish Farming in the Northern Region of Iraq

Abstract: In the '80s, Kuwait operations and the conflict between Iran and Iraq negatively affected the aquaculture and especially fish farming. This study was carried out to analyze fish productions and advancements in its development in the Northern Region of Iraq. Also, this study was aiming at obtaining the estimates of the production function for fish production and total income. The study involved 60 farms. Data were analyzed by using descriptive statistics, variance analysis and multiple regression. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…BCR was used in previous studies to evaluate the viability of fish farming (Namonje-Kapembwa and Samboko, 2020). Researchers calculated the benefit-cost ratio between 1.05 and 1.9 in the fish farming sector in previous studies (Janssen et al, 2017;Sharma et al, 2018;Tunde et al, 2015;Maaruf and Akbay, 2020). The obtained results were consistent with the results of other studies, and it can be concluded that seabass farming is profitable in Turkey.…”
Section: Discussionsupporting
confidence: 81%
“…BCR was used in previous studies to evaluate the viability of fish farming (Namonje-Kapembwa and Samboko, 2020). Researchers calculated the benefit-cost ratio between 1.05 and 1.9 in the fish farming sector in previous studies (Janssen et al, 2017;Sharma et al, 2018;Tunde et al, 2015;Maaruf and Akbay, 2020). The obtained results were consistent with the results of other studies, and it can be concluded that seabass farming is profitable in Turkey.…”
Section: Discussionsupporting
confidence: 81%
“…Fish farming projects are among the best investment projects in Iraq and clearly support food security (10), fish farmers face the challenges of feed costs, which constitute 65-76% of the production cost, the researchers worked to try to reduce this percentage by finding alternatives to the ingredients of the diets, through available and low-cost food additives and testing their addition in part or as a substitute for one of the components of the diet (7). Canola oil is available globally in abundance and at an affordable cost compared to other food oils (3), in addition, it contains essential fatty acids in ideal quantities in feeding aquatic animals (18), it was noted that the use of canola oil partially or completely in fish diets feeding of common carp gave significant results in growth indicators, liver health indicators, hepatosomatic index (HSI), economic index, survival rates and net lipid utilization (NLU) (12), we can use food non-protein sources such as carbohydrates and fats to balance energy, they can reduce the consumption of protein to produce energy for the fish, which can be deposited in the muscles of the body and increase the weight of the fish (1).…”
Section: Introductionmentioning
confidence: 99%